Bacterial Toxins: Genetics, Cellular Biology and Practical Applications. Edited by Thomas Proft. Issue 18 (20th November 2013) - Weiss, Alison
<x xml:space="preserve">Abstract</x> Caister Academic, Norwich, 2013, VIII+234 pp., hardcover, £ 159.00.—ISBN 978‐1‐908230‐28‐7